Fracture behaviour of metal powder compact / Suraya Mohd Tahir, Ahmad Kamal Ariffin and N. Muhamad - S.M., Tahir; A.K., Ariffin; N., Muhamad (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2006)
This paper is intended to establish a fracture criterion for metal powder compact during the cold compaction process. Based on the fracture criterion of granular materials in compression, a displacement based finite element model has been developed to analyse fracture initiation and crack growth in iron powder compact. Estimation of fracture toughness variation with relative density is established in order to provide the fracture parameter as compaction proceeds. A crack initiated from the boundary of iron powder compact is considered in this work. The finite element simulation of the crack propagation reveals that crack propagates in the direction of higher shear stress and higher relative density. This also implies that the crack grows in the direction where the compaction pressure is much higher, which is in line with the conclusion made by previous researchers on shear crack growth in materials under compression.